2020
DOI: 10.1016/j.nmni.2020.100739
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and phylogenetic analysis of Vibrio cholerae genotypes in Hillah, Iraq

Abstract: Vibrio cholerae is a cause of serious endemic diarrhoea associated with cholera in many regions in the world. A total of 256 stool and rectal swabs were collected from patients suspected to have cholera admitted to three hospitals in Hillah, Babylon Governorate, Iraq, for the period 1 September to 29 December 2017. After the routine culture of samples for isolation and identification of V. cholerae isolates, PCR was performed for molecular detection of V. cholerae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Huq et al 14 reported that molecular detection approaches had enhanced the incidence of finding harmful microbes while conventional culture-based detection methods might have failed. Many authors endorsed the using of 16S rDNA gene to identify Vibrio spp [15][16][17][18] . In addition, the genetic information gained from the sequencing of the ctx and toxR genes distinguishes between species that are closely related, such as V. cholerae and V. parahaemolyticus 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Huq et al 14 reported that molecular detection approaches had enhanced the incidence of finding harmful microbes while conventional culture-based detection methods might have failed. Many authors endorsed the using of 16S rDNA gene to identify Vibrio spp [15][16][17][18] . In addition, the genetic information gained from the sequencing of the ctx and toxR genes distinguishes between species that are closely related, such as V. cholerae and V. parahaemolyticus 19 .…”
Section: Discussionmentioning
confidence: 99%